Analysis Of Ihsan Values And 360-Degree Evaluation For Talent Mapping At Masyithoh Islamic Hospital Bangil - Nanang Riono wahyudi; Pipit Festi; Yudied Rahmat (LP2IHKI UMSurabaya, 2025)
Objective: Masyithoh Islamic Hospital (RSI) Bangil applies Sharia-based ethics in human resource (HR) management, with ihsan - the perfection of worshiping Allah as if one were seeing Him - as its guiding principle. Ihsan is operationalized through six indicators: Working Perfectly, Repaying Goodness with Greater Good, Preventing Harm, Future-Oriented Investment, Providing Solutions When Justice Is Not Fulfilled, and Consequence of Faith. This study examined the integration of ihsan-based indicators with 360-degree evaluation as performance appraisal and talent mapping tools. Methods: Using a descriptive-analytic design With One-way ANOVA test, data were collected from 119 employees through purposive sampling and three waves of talent mapping in October 2025. The 9-Box Talent Grid combined potential (ihsan behavior, analytical-creative, psychological tests) and performance (360° evaluation). Results: showed 64.7% of employees in Box 5 (expected performance, medium potential), with high ihsan potential (82.22) but lower analytical skills (69.60). Only 2.52% demonstrated high potential, while 21.2% were in risk zones. The model proved effective for talent identification, though constrained by analytical capacity, and supports recommendations for upskilling and succession planning to strengthen organizational performance. Conclusion: The study confirms that integrating Ihsan values with 360-degree evaluation is effective for talent mapping at Masyithoh Islamic Hospital Bangil. Employees showed strong Ihsan potential but weaker analytical skills, placing most in medium-potential categories. This model highlights the value of Sharia-based ethics in HR management and underscores the need for targeted upskilling and succession planning to enhance organizational performance.